O trabalho informal no comércio popular : ressignificando práticas na nova cultura do trabalho - Rangel, Felipe (Universidade Federal de São Carlos, 2015)
This study relies on the occupational trajectories of workers engaged in popular ways of trade. As background, we have the capitalist transformations in the latest’s decades, which resulted in economical, technological and cultural changes that affected deeply the position of work as a constructor of identities and social values. It is noticed that the precariousness of the formal work relationships associated to the dissemination of the ideology of entrepreneurship has resulted in the search for occupational and income alternatives that weakened the frontiers between formal and informal. In this scenario, the demarcations amidst legal and illegal also became less evident and significant. This way, we discuss the insertion of agents in informal economical activities – as those exercised by street venders -, trying to escape viewing unemployment or precariousness in the labor market as main reasons to exert those occupations. Taking into consideration the subjectivity of the situations, we try to think over the influence of an entrepreneur reasoning under the subjects conduct. From the recovery of the occupational trajectories of agents involved in different popular trade grades, we seek to understand the worker’s perception about his own occupation and the values attributed to those forms of work in the contemporary world, considering that, even though traditional, these activities have been through reconfigurations of its practice and meaning in front of the new economic and cultural context on which it is presented.
Keywords: Comércio popular; Globalização por baixo; Nova informalidade; Empreendedorismo; Cultura do trabalho; Popular trade; Globalization from below; New informality; Entrepreneurship; Culture of work; CIENCIAS HUMANAS::SOCIOLOGIA::OUTRAS SOCIOLOGIAS ESPECIFICAS